Total Synthesis of a Marine Alkaloid—Rigidin E - Qiang Xiao; Xiaoji Wang; Ruchun Yang; Haixin Ding; Banpeng Cao (Marine Drugs, 2012)
In the present paper, we report an efficient total synthesis of a marine alkaloid, rigidin E. The key tetrasubstituted 2-amino-3-carboxamidepyrrole intermediate was synthesized by cascade Michael addition/intramolecular cyclization between N-(2-(4-(benzyloxy)phenyl)-2-oxoethyl)methanesulfonamide and 3-(4-(benzyloxy)phenyl)-2-cyano-N-methylacrylamide. Subsequent carbonylation with triphosgene catalyzed by I2 and deprotection of benzyl groups afforded rigidin E in 21% overall yield. This strategy has the merits of metal-free reactions, low cost, mild reaction protocols, and easy access to diversity-oriented derivatives for potential structure-activity relationship investigation.